Calculator search results

Formula
Solve the equation
Graph
$y = - \dfrac { x } { 3 } + 4$
$y = - 2$
$x$-intercept
$\left ( 12 , 0 \right )$
$y$-intercept
$\left ( 0 , 4 \right )$
$- \dfrac{ x }{ 3 } +4 = -2$
$x = 18$
 Solve a solution to $x$
$\color{#FF6800}{ - } \color{#FF6800}{ \dfrac { x } { 3 } } \color{#FF6800}{ + } \color{#FF6800}{ 4 } = \color{#FF6800}{ - } \color{#FF6800}{ 2 }$
 Multiply both sides by the least common multiple for the denominators to eliminate the fraction 
$\color{#FF6800}{ - } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 12 } = \color{#FF6800}{ - } \color{#FF6800}{ 6 }$
$- x \color{#FF6800}{ + } \color{#FF6800}{ 12 } = - 6$
 Move the constant to the right side and change the sign 
$- x = - 6 \color{#FF6800}{ - } \color{#FF6800}{ 12 }$
$- x = \color{#FF6800}{ - } \color{#FF6800}{ 6 } \color{#FF6800}{ - } \color{#FF6800}{ 12 }$
 Find the sum of the negative numbers 
$- x = \color{#FF6800}{ - } \color{#FF6800}{ 18 }$
$\color{#FF6800}{ - } \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 18 }$
 Change the sign of both sides of the equation 
$\color{#FF6800}{ x } = \color{#FF6800}{ - } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 18 } \right )$
$x = \color{#FF6800}{ - } \left ( \color{#FF6800}{ - } 18 \right )$
 Simplify Minus 
$x = 18$
 그래프 보기 
Graph
Solution search results
Have you found the solution you wanted?
Try again
Try more features at QANDA!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture